2018
DOI: 10.7150/ijms.25656
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose inhibits H2O2-induced autophagic death in dopaminergic SH-SY5Y cells via mitigation of ROS-dependent endoplasmic reticulum stress and AMPK activation

Abstract: Autophagy is a catabolic process to maintain intracellular homeostasis via removal of cytoplasmic macromolecules and damaged cellular organelles through lysosome-mediated degradation. Trehalose is often regarded as an autophagy inducer, but we reported previously that it could prevent ischemic insults-induced autophagic death in neurons. Thus, we further investigated in this study whether trehalose could protect human dopaminergic SH-SY5Y cells against H2O2-induced lethal autophagy. We found pretreatment with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 51 publications
2
16
1
Order By: Relevance
“…This was likely caused by increased Tre activities. In addition, trehalose restrained the H 2 O 2 ‐induced increase of intracellular ROS (Gao et al, 2018), indicating that trehalose level changes are likely related to response to biotic stress. Extracellular trehalose is potentially a signal of insect attack (Singh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This was likely caused by increased Tre activities. In addition, trehalose restrained the H 2 O 2 ‐induced increase of intracellular ROS (Gao et al, 2018), indicating that trehalose level changes are likely related to response to biotic stress. Extracellular trehalose is potentially a signal of insect attack (Singh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence further demonstrated that H 2 O 2 -induced mitochondrial membrane depolarization, swelling, and fragmentation could be due to the motility of mitochondria accompanied with mitochondrial elongation (Debattisti et al, 2017 ). Moreover, evidence showed that H 2 O 2 could induce autophagic death in dopaminergic SY5Y cells through ROS-dependent endoplasmic reticulum stress and AMPK activation (Gao Z. et al, 2018 ). Therefore, it is of importance to identify a mechanism that exerts neuroprotective effects against oxidative injury.…”
Section: Introductionmentioning
confidence: 99%
“…Even if trehalose is an autophagy enhancer it is difficult to explain how trehalose could produce neuroprotection in a toxin-lesioned model of PD, such as 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) (Sarkar et al, 2014), without additional actions. Several other effects of trehalose, independent of autophagy, have also been suggested to confer the neuroprotective effects of trehalose, including being a chemical chaperone (Crowe, 2007;Sarkar et al, 2014), downregulation of poly(ADP-ribose) polymerase (Spina-Purrello et al, 2010), regulation of stress granules (Dimasi et al, 2017), anti-inflammatory actions (Echigo et al, 2012;Pagliassotti et al, 2017;Mirzaie et al, 2018), inducer of neurotrophic factors (Perucho et al, 2016;Portbury et al, 2017a,b), and reduction of oxidative stress (Gao et al, 2018;Mizunoe et al, 2018). Any one of these mechanisms, or more likely a combination of several of these mechanisms, may be responsible for the neuroprotective effects of trehalose.…”
Section: Introductionmentioning
confidence: 99%